La mimesi dell’Altro nella narrativa di Giuseppe Culicchia - Puto, Małgorzata (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
The objective of the study is to identify and examine the essential elements whichconstitute the concept of the Other in the novels of Giuseppe Culicchia. The texts analyzedwere published by Culicchia, writer, essayist and translator in Turin, Italy, from 1994 to2019. The theoretical literary perspective is that of mimesis (Erich Auerbach, Zofia Mitosek,Nicoletta Salomon, Cesare Segre) and the concept of the l’Altro derives from anthropologicalstudies (Marc Augé, Marco Aime, Ugo Fabietti, Francesco Remotti). The purpose ofthis study is to promote interdisciplinary research and to present the model of the Otherand its evolution in novels. The article focuses on aspects of otherness, more apparent inCulicchia, that is to say: distance and space (the idea of nonluogo, mente locale, mobility),set of values and the consequent changes in the characters of his novels.